Directly Measured Costs of Severe Maternal Morbidity Events during Delivery Admission Compared with Uncomplicated Deliveries - Debbink, Michelle P.; Metz, Torri D.; Nelson, Richard E.; Janes, Sophie E.; Kroes, Alexandra; Begaye, Lori J.; Heuser, Cara C.; Smid, Marcela C.; Silver, Robert M.; Varner, Michael W.; Einerson, Brett D. (American Journal of Perinatology, 2021)
Objective To estimate the actual excess costs of care for delivery admissions complicated by severe maternal morbidity (SMM) compared with uncomplicated deliveries.Study Design This is a retrospective cohort study of all deliveries between October 2015 and September 2018 at a single tertiary academic center. Pregnant individuals ≥ 20 weeks' gestation who delivered during a hospital admission (i.e., a “delivery admission”) were included. The primary exposure was SMM, as defined by Centers for Disease Control and Prevention (CDC) criteria, CDC criteria excluding blood transfusion, or by validated hospital-defined criteria (intensive care unit admission or ≥ 4 units of blood products). Potential SMM events identified via administrative and blood bank data were reviewed to confirm SMM events had occurred. Primary outcome was total actual costs of delivery admission derived from time-based accounting and acquisition costs in the institutional Value Driven Outcomes database. Cost of delivery admissions with SMM events was compared with the cost of uncomplicated delivery using adjusted generalized linear models, with separate models for each of the SMM definitions. Relative cost differences are reported due to data restrictions.Results Of 12,367 eligible individuals, 12,361 had complete cost data. Two hundred and eighty individuals (2.3%) had confirmed SMM events meeting CDC criteria. CDC criteria excluding transfusion alone occurred in 1.0% (n = 121) and hospital-defined SMM in 0.6% (n = 76). In adjusted models, SMM events by CDC criteria were associated with a relative cost increase of 2.45 times (95% confidence interval [CI]: 2.29–2.61) the cost of an uncomplicated delivery. SMM by CDC criteria excluding transfusion alone was associated with a relative increase of 3.26 (95% CI: 2.95–3.60) and hospital-defined SMM with a 4.19-fold (95% CI: 3.64–4.83) increase. Each additional CDC subcategory of SMM diagnoses conferred a relative cost increase of 1.60 (95% CI: 1.43–1.79).Conclusion SMM is associated with between 2.5- and 4-fold higher cost than uncomplicated deliveries.Key Points
Keywords: severe maternal morbidity; cost; value